2002
DOI: 10.1021/jp020574l
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Fluorescence Dynamics of Flavoproteins:  Comparative Studies on Flavodoxin, Its Site-Directed Mutants, and Riboflavin Binding Protein Regarding Ultrafast Electron Transfer in Protein Nanospaces

Abstract: We have studied the fluorescence dynamics of “nonfluorescent” flavoproteins including flavodoxin (FD), its mutants W60F, Y98F, and W60F/Y98F, and riboflavin binding protein (RBP) with the femtosecond fluorescence up-conversion method and have observed the fluorescence quenching dynamics of FD and its mutants for the first time. The strong fluorescence quenching in these flavoproteins seems to be caused by ultrafast electron transfer (ET) from aromatic amino acid residues to the excited flavin chromophore in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 14 publications
7
124
1
Order By: Relevance
“…Furthermore, the pattern of positive and negative absorbance changes shows distinctive differences: the intensive negative signal of the stimulated emission at 520 -600 nm observed for free riboflavin in aqueous solution is missing for HsDod A -bound riboflavin (2), and the positive signal does not reach that far into the long wavelength region above 700 nm. A discussed mechanism for the fast quenching of the excited state, on the basis of previous investigations on flavoproteins (9,18,19), is an ultrafast electron transfer from a tryptophan residue to the excited flavin. If such an electron transfer occurs, the spectrum should show the absorption characteristics of a cationic tryptophan radical, expected around 560 nm (38,39) and of an anionic flavosemiquinone around 510 nm (40 -42).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the pattern of positive and negative absorbance changes shows distinctive differences: the intensive negative signal of the stimulated emission at 520 -600 nm observed for free riboflavin in aqueous solution is missing for HsDod A -bound riboflavin (2), and the positive signal does not reach that far into the long wavelength region above 700 nm. A discussed mechanism for the fast quenching of the excited state, on the basis of previous investigations on flavoproteins (9,18,19), is an ultrafast electron transfer from a tryptophan residue to the excited flavin. If such an electron transfer occurs, the spectrum should show the absorption characteristics of a cationic tryptophan radical, expected around 560 nm (38,39) and of an anionic flavosemiquinone around 510 nm (40 -42).…”
Section: Resultsmentioning
confidence: 99%
“…The picosecond time scale of these events indicates that the residue(s) involved in the transfer must be in close proximity to the isoalloxazine ring of the flavin. Previous studies on flavo-enzymes have revealed that rapid light-driven ET may occur from aromatic residues to flavin (25,26). Tyr-8 (Tyr-21 in AppA) is a good candidate because it is the closest aromatic residue to the flavin and has been shown to be critical for photocycling activity in BLUF domains (12,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…This result sets it apart from most other flavoproteins, whose flavin cofactor is normally oxidized or fully reduced and whose catalytic mechanism does not require light. ''Artificial'' electron transfer starting from excited oxidized or fully reduced flavins has been studied in several flavoproteins (18)(19)(20), whereas redox photochemistry of flavin radicals is so far only known for photolyase.…”
mentioning
confidence: 99%